The Impact of AI-Driven Gamification on Student Engagement and Academic Performance in English Language Teaching - Uzma Safdar; Sidra Shafi; Mariyam Junaid (Indus Journal of Social Sciences, 2025)
The integration of gamification and artificial intelligence (AI) in English Language Teaching (ELT) has revolutionized traditional pedagogical approaches by fostering interactive, personalized, and adaptive learning experiences. This paper investigates the effects of AI-based gamification on student involvement and academic performance in ELT classrooms. Data were collected using a mixed-methods approach during which English language learners and instructors completed surveys, classroom observations were conducted, and semi-structured interviews administered. AI-enhanced gamified language learning shows better motivation, engagement, and retention highlights. All the learning features are customized through adaptive methods across the four stages. But challenges included over-reliance on technology, accessibility issues and the need for teacher training. The study concludes by offering pedagogical implications for educators and policymakers seeking to integrate AI-enhanced gamification into ELT curricula to maximize student engagement and language proficiency.